The design of lighting - Tregenza, Peter; Loe, David (Routledge, 2014)
"This fully updated edition of the successful book The Design of Lighting, provides the lighting knowledge needed by the architect in practice, the interior designer and students of both disciplines. The new edition offers a clear structure, carefully selected material and linking of lighting with other subjects, in order to provide the reader with a comprehensive and specifically architectural approach to lighting. Features of this new edition include: technical knowledge of lighting in the context of architectural design; an emphasis on imagination in architectural light and presentation of the tools necessary in practice for creative design; additional chapters on the behaviour of light and on the context of design; a strong emphasis on sustainable design and energy saving, with data and examples; analyses of actual lighting schemes and references to current standards and design guides; an up-to-date review of lamp and lighting technology, with recommendations on the choice of equipment; a revision of the calculation section, with examples and step-by-step instructions, based on recent student feedback about the book"--Provided by publisher.